Age-based formulae to estimate children's weight in the emergency department. Issue 5 (13th October 2010) - Cattermole, G N; Leung, Mia P Y; So, H-K; Mak, P S K; Graham, C A; Rainer, T H
Abstract : Objective: To develop an age-based weight estimation rule in a Chinese population and to compare its performance with existing formulae. Design: Population-based observational study. Setting: Schools and kindergartens in Hong Kong. Subjects: Healthy Chinese children aged 1–10 years old on their last birthday. Interventions: Weight was measured to the nearest 0.2 kg. Main outcome measures: Linear regression was used to derive a simple formula relating weight to the child's age on his or her last birthday. The accuracy and precision of different age-based weight formulae was compared using coefficient of variation, Bland Altman plots, and by determining the proportion of children with estimates >30% outside the actual weight. Results: The Chinese Age Weight Rule is a simple linear formula that is more accurate than and at least as precise as any other age-based weight estimation rule: weight in kg=(3×age last birthday)+5. It is accurate and precise in children <7 years old, but all age-based weight estimates are imprecise in older children. Conclusions: The Chinese Age Weight Rule should be used in a Chinese population in preference to any other age-based weight estimation rule. Caution should be taken when using it in older children in whom other weight-estimation tools may be more appropriate.